Direct Detection of Voltage Collapse - Ahmed Nasser B. Alsammak (Tikrit Journal of Engineering Sciences, 2013)
Voltage stability is indeed a dynamic problem. Dynamic analysis is important for  better understanding of voltage instability process. In this work an analysis for voltage stability from bifurcation and voltage collapse point of view based on a center manifold voltage collapse model. A static and dynamic load models were used to explain voltage collapse. The basic equations of  simple power system and load are used to demonstrate voltage collapse dynamics and bifurcation theory. These equations are also developed in a manner, which is suitable for the Matlab-Simulink application. Detection of voltage collapse before it reaches the critical collapse point was obtained in simulation results.